The Content Analysis of Learning Curriculum during Covid -19 Period at Islamic Senior High School of Assalaam Modern Islamic Boarding School Sukoharjo - Rahma, Freda Yunia (International Islamic Schools Alliance, 2021)
One of the aspects of education in a pandemic during the Covid-19 period is about the learning curriculum of the school. In this regard, the researcher analyzed the content of the curriculum for the 2019-2020 period before the pandemic and during the pandemic which began in early March 2020 at Islamic Senior High School Assalaam Islamic Boarding School Sukoharjo Indonesia. This research used a qualitative approach with Spradley’s data analysis method with a domain analysis, a taxonomic analysis, a component analysis, and carries out a theme. Data collecting techniques is interviews, observation and documentation. The results of the research are referred to the learning curriculum initially focused on the methods such as classroom learning with the group work method. Completeness of learning for this period of the pandemic, it was decided to the completeness for all subjects by completing the entire learning program report for six semesters and obtaining a minimum good attitude or behaviour score. Meanwhile, the school has to change the learning process by using digital learning applications such as e-learning and choosing creative and innovative methods from the teachers for learning objectives in these emergency conditions. In this aspect, the schools are dealing with new things by filling in the basis of online examinations and considering learning completeness by adjusting the essence of each subject to be a priority in the learning of all students. This research is needed to test the readiness of education policy holders in curriculum preparation when a pandemic occurs in the world.